Family Values: The Trapp Family Singers in North America, 1938-1956 - Saffle, Michael (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2004)
Overlooked or ignored for decades by music historians and specialists in performance practices, the real-life Trapp Family Singers achieved enormous success especially in Canada and the United States during the late 1930s, 1940s, and early 1950s through their appeal to—and consequent reception in terms of—"family values." These values included, but were not altogether limited to, the Trapp's Christian faith, patriotic activities, and contributions to charitable causes, as well as the wholesome image associated with the family's private lives, their Vermont "Sing Weeks," and their more than 1,800 estimated concert appearances.